Study of microstructural variation with annealing temperature of Ti–Al–C films coated on stainless steel substrates. (24th January 2020) - Abbas, Nadeem; Qin, Xiande; Ali, Shoukat; Zhu, Guangming; Yi, Zheng; Yang, Xinge; Zeng, Xierong; Ullah, Zaka; Gu, Kunming; Tang, Jiaoning
Abstract: Bipolar plates (BPs) are key component of a fuel cell and the high prices of fuel cell are owed to the use of expensive BPs. Metals are cheap alternate to the conventional thicker and expensive graphitic BP plates. Stainless steel (SS) is considered to be the most suitable future BP material but highly corrosive nature of metals prevents their direct use as BPs, so surface treatment is obligatory. Ti–Al–C is an important ternary metal carbide which possess various unique and useful properties and could be considered as an effective coating material for SS BPs. Since the film properties are sensitive to the substrate type, so a detailed investigation about the morphology and microstructure of Ti–Al–C films, deposited on two different substrates (SS304 and SS316) by a combined ECR-CVD and PVD system, as a function of annealing temperature is reported hereby. It was observed that change in microstructure is diverse for different substrates with annealing temperature. Moreover, the formation of Ti2 AlC MAX phase along with other phases was also recognized at an annealing temperature of 700 °C. Our study provides an insight about the variation in morphology and microstructure of Ti–Al–C thin films on SS substrates with annealing temperature. Highlights: Stainless steel (SS) requires protective coating for fuel cell applications. Ti–Al–C films are coated on SS304 and SS316 by a scale-able method. Annealing temperature renders varied morphology and microstructure.